OpenGL essentials LiveLessons : sneak peek video training - Varcholik, Paul (LiveLessons., 2014)
"5+ Hours of Video Instruction Graphics programming is prevalent in many aspects of modern software development; and the need for graphics programmers is perhaps most felt with the explosion of game and graphics-oriented apps. OpenGL is at the center of this new wave of graphics-oriented programming as the chief rendering library for cross-platform development. Quality educational material is a necessity for newcomers to the field. OpenGL Essentials LiveLessons introduces viewers to graphics programming through a moderately deep-dive into shader programming and the OpenGL API. Dr. Paul Varcholik guides viewers with a practical, hands-on approach to modern OpenGL application development. While these videos are geared towards programmers, no prior knowledge of graphics programming or 3D math is required. The lessons begin with "Hello, World!" style rendering (drawing a single point and triangle) and extend into introductory lighting models including ambient and diffuse lighting, specular highlights, point lights, and spot lights. The videos also cover texture mapping, environment mapping, normal mapping, and color blending and introduce viewers to 3D math in a straight-forward, stress-free fashion. Dr. Paul Varcholik is a twenty year veteran of the software development industry and has spent the past ten years writing video games. He was a lead software engineer at Electronic Arts working on titles including John Madden NFL Football and Superman Returns. He is currently a programming instructor at the Florida Interactive Entertainment Academy (FIEA)--a graduate degree program in game development at the University of Central Florida. Paul is also the author of Real-Time 3D Rendering with DirectX 11 and HLSL: A Practical Guide to Graphics Programming."--Resource description page.